The Influence of Training, Work Discipline, and Organizational Culture on Employee Productivity at PT Golden Communication Batam Region - Febriliani Lutfi Latifah; Rini Elfina; Netti Syafitri (SEAN Institute, 2026)
The underlying phenomenon of this research is the fluctuation of productivity targets and the need to improve the quality of human resources to face competition in the telecommunications industry. The research method used was a quantitative approach, with data collection techniques through distributing questionnaires to 60 respondents, employees of PT. Golden Communication, Batam Region. Data analysis techniques used multiple linear regression analysis, classical assumption tests, and hypothesis testing (ttests and F-tests) using SPSS software. The results of the study partially indicate that the Training variable has a positive and significant effect on Employee Productivity with a calculated t-value of 4.790. The Work Discipline variable has a positive and significant effect on Employee Productivity with a calculated t-value of 2.685. The Organizational Culture variable also has a positive and significant effect on Employee Productivity with a calculated t-value of 2.281. Simultaneously (together), these three variables significantly influence productivity, with an F-value of 14.649. The coefficient of determination (Rsquare) of 0.440 indicates that training, work discipline, and organizational culture contribute 44% to employee productivity, while the remaining 56% is influenced by other factors not examined in this study.